2017
DOI: 10.1080/09593985.2017.1289578
|View full text |Cite
|
Sign up to set email alerts
|

Do Pilates-based exercises following total knee arthroplasty improve postural control and quality of life?

Abstract: Pilates-based exercises performed along with standard exercise programs were more effective for improving balance and quality of life than standard exercise programs alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
0
19
0
4
Order By: Relevance
“… 46 An observational study noted that women who were inactive prior to TKA had increased odds of having mobility limitations and dying by age 85. 47 Studies of specific types of exercise regimens (aquatic exercise, 48 , 49 Pilates, 50 tai chi chuan 51 ) following TKA have shown positive effects on a variety of outcomes, including health-related quality of life, walking distance, balance, and physical function. One study examining a resistance exercise regimen 4 years following TKA demonstrated benefits of increased strength as well as increased walking speed and physical function.…”
Section: Physical Activity ♦◊◊◊mentioning
confidence: 99%
See 1 more Smart Citation
“… 46 An observational study noted that women who were inactive prior to TKA had increased odds of having mobility limitations and dying by age 85. 47 Studies of specific types of exercise regimens (aquatic exercise, 48 , 49 Pilates, 50 tai chi chuan 51 ) following TKA have shown positive effects on a variety of outcomes, including health-related quality of life, walking distance, balance, and physical function. One study examining a resistance exercise regimen 4 years following TKA demonstrated benefits of increased strength as well as increased walking speed and physical function.…”
Section: Physical Activity ♦◊◊◊mentioning
confidence: 99%
“…Five high-quality studies 56–60 and 1 moderate-quality study 61 addressed different aspects of movement retraining after TKA. These studies varied in the types of interventions but included dynamic balance training, 56 , 59 robot-assisted gait retraining, 61 movement training with visual biofeedback to promote weight-bearing symmetry, 50 or motor functional training. 58 …”
Section: Motor Function Training (Balance Walking Movement Symmetrymentioning
confidence: 99%
“…Observing all these variables, we cannot fail to evaluate how the stomatognathic system, more precisely the oral conditions behave in face of the impact on the health and quality of life of the patients. These two terms, health and quality of life, are extremely close, where health contributes to improve the quality of life, being fundamental in the physical and emotional balance of the human being [40].…”
Section: Ethical Statementmentioning
confidence: 99%
“…The control of large group muscles with coordination, and focusing on breathing may increase aerobic capacity (Caldwell, Harrison, Adams, & Triplett, 2009), and further improve mental health (Kucuk & Livanelioglu, 2015). Heretofore, some researchers have also reported that the holistic approach of Pilates based training may offer physical and psychological improvements for human health (Akbas & Erdem, 2016;Bernardo, 2007;Cruz-Ferreira et al, 2011;Karaman, Yuksel, Kinikli, & Caglar, 2017;Kucuk & Livanelioglu, 2015), and various intensities benefit quality of life, mental health, fatigue, physical fitness levels, and body types in diverse rates (Anderson & Spector, 2000;Arslan, Çakmakçi, Taşkin, Çakmakçi, & Ismet, 2012;Ashrafinia et al, 2015;Caldwell et al, 2009;Campos de Oliveira, Gonçalves de Oliveira, & Pires-Oliveira, 2015;Cruz-Ferreira et al, 2011;Frank, Edwards, & Larimore, 2017;Ginsberg et al, 2016;Hassan & Amin, 2011;Kucuk & Livanelioglu, 2015;Leopoldino et al, 2013;McGrath, O'Malley, & Hendrix, 2011;Memmedova, 2015;Miller & Mesa, 2013;Pourvaghar, Bahram, Sharif, & Sayyah, 2014;Rogers & Gibson, 2009;Roh, 2016;Segal, Hein, & Basford, 2004;Shanazari, Marandi, & Minasian, 2013;Soysal Tomruk, Uz, Kara, & Idiman, 2016;Stan et al, 2012;Şavkın, 2014;Vieira, Faria, Wittmann, Teixeira, & Nogueira, 2013). The method is recommended by health professionals, both as rehabilitative for the people who have diseases, and preventive for undiagnosed or healthy individuals…”
Section: Introductionmentioning
confidence: 99%